Research on High-Precision and Wide-Range Spacecraft Potential Measurement Method Based on Capacitive Voltage Division - Yin, Hong; Liu, Haibo; Qin, Xiaogang; Liu, Qing; Wang, Jun; Wen, Xuan; Wang, Peng; Yu, Zixin; Yang, Shengsheng (Sensors (Basel, Switzerland), 2024)
The charging and discharging of satellite surfaces induced by the space plasma environment constitute a primary cause of spacecraft anomalies, particularly in geosynchronous orbits subject to geomagnetic substorms and hot plasma injections from the magnetotail, where satellites are prone to unequal high-potential charging, significantly impacting the safe and reliable operation of spacecraft. Addressing the need for measuring these unequal charge states, a high-precision, wide-range spacecraft potential measurement method based on capacitive voltage division was investigated. This study analyzed the mechanism of potential measurement and the factors contributing to errors during the measurement process, explored optimal design methodologies, and innovatively developed a fundamental charge zeroing method to resolve output drift issues caused by accumulated errors fundamentally. Consequently, a non-contact potential measurement system was developed, featuring a measurement range of up to −15,000 V, a resolution below 15 V, and a nonlinear error of less than 0.1%. This system provides technical support for monitoring the potential state of spacecraft and ensuring their safety and protection.